The lot of the unemployed: a time use perspective - Alan B. Krueger; Andreas Mueller (Institute for the Study of Labor (IZA), 2008)
This paper provides new evidence on time use and subjective well-being of employed and unemployed individuals in 14 countries. We devote particular attention to characterizing and modeling job search intensity, measured by the amount of time devoted to searching for a new job. Job search intensity varies considerably across countries, and is higher in countries that have higher wage dispersion. We also examine the relationship between unemployment benefits and job search.
urn:nbn:de:101:1-20080527107
Keywords: J64; 330; Unemployment; job search; time use; unemployment benefits; inequality; Arbeitslosigkeit; Arbeitsuche; Zeitbudgetforschung; Arbeitslosenversicherung; Lohnstruktur; EU-Staaten; USA